2022
DOI: 10.1002/imt2.5
|View full text |Cite
|
Sign up to set email alerts
|

ImageGP: An easy‐to‐use data visualization web server for scientific researchers

Abstract: Data visualization plays a crucial role in illustrating results and sharing knowledge among researchers. Though many types of visualization tools are widely used, most of them require enough coding experience or are designed for specialized usages, or are not free. Here, we present ImageGP, a specialized visualization platform designed for biology and chemistry data illustration. Highlights• Publication-quality visualization results.• Easy to use and customize.• Reproducible results with scripts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
180
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(180 citation statements)
references
References 17 publications
0
180
0
Order By: Relevance
“…The KEGG pathway analysis suggested that the genes are predominantly involved in different cancer pathways, development of bladder cancer, oncogenic virus infection pathways and so on. These findings again signify that the PSMC family genes may be associated with LUAD development and progression since the deregulation of the activity of PSMC s’ co-expressed genes in LUAD tissues can result in the initiation of oncogenic processes [42]. As a result, the co-expressed genes of the PSMC s could also be investigated in LUAD therapeutic and diagnostic measures discovery.…”
Section: Discussionmentioning
confidence: 85%
“…The KEGG pathway analysis suggested that the genes are predominantly involved in different cancer pathways, development of bladder cancer, oncogenic virus infection pathways and so on. These findings again signify that the PSMC family genes may be associated with LUAD development and progression since the deregulation of the activity of PSMC s’ co-expressed genes in LUAD tissues can result in the initiation of oncogenic processes [42]. As a result, the co-expressed genes of the PSMC s could also be investigated in LUAD therapeutic and diagnostic measures discovery.…”
Section: Discussionmentioning
confidence: 85%
“…All R packages were installed via Bioconductor (version 1.30.16) [ 20 ]. Overlapping diagrams were produced by VennDiagrams pot ( , accessed around 13 April 2022) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Nearest Sequenced Taxon Index (NSTI) score was determined for each sample to evaluate the prediction accuracy of PICRUSt [ 54 ], and a lower value (roughly < 0.06) indicated that the functional profiles obtained were closely related to the reference genome. PCA was employed to group or separate samples using ImageGP [ 55 ] based on the function abundance of KEGG pathways on three levels. Significantly different KEGG pathways on level II between two salinity clusters were determined by Statistical Analysis of Metagenomic Profiles (STAMP) [ 56 ], using two-sided Welch’s t test with a Storey (normal distribution) or Benjamini–Hochberg (abnormal distribution) FDR multiple testing correction [ 57 ] (adjusted q value < 0.05).…”
Section: Methodsmentioning
confidence: 99%